Pengembangan Media Pembelajaran Vidioscribe untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPS di SMP Negeri 2 Hu’u - Sumiyati Sumiyati; Husnul Khatimah; Pupu Insaniah; Nurhayati Nurhayati; Fijriani Fijriani (UIN Fatmawati Sukarno Bengkulu, 2024)
The development of information and communication technology makes it easier for us to access everything, for this we need the competence of each person in mastering various science and technology (IPTEK). As educators, teachers must be able to develop themselves in developing the learning media used in class. The aim of this research is to test the validity, practicality and effectiveness of videoscribe media on the learning outcomes of class VII students at SMP Negeri 2 Hu'u. Researchers developed videoscribe learning media to help students study social sciences (IPS). This type of research uses Research and Development, using the ADDIE model. The sample in this study was 36 class VII students at SMP Negeri 2 Hu'u. The data collection instruments used were interviews, questionnaires and tests. The data analysis techniques used are media validity analysis, media practicality analysis, and media effectiveness analysis. The research results showed that the validity of the media and material was 86% in the